ASSESSING SOCIO-CULTURAL AND RELIGIOUS NORMS ASSOCIATED WITH SEXUAL BEREAVEMENT FOLLOWING A CHILD’S LOSS AMONG COUPLES OR PARENTS - Zembe, Asanda; Kang’ethe, Simon Murote (Journal of Ecohumanism, 2026)
The article aimed to discuss socio-cultural and religious norms associated with sexual bereavement following a child’s loss among couples or parents in the Didi Location of the Eastern Cape. The article investigated 12 samples using a qualitative approach, a descriptive and explorative research design, and phenomenology as a specific research study. Stroeb and Schut’s dual process model gave the article a theoretical framework. Findings established that mourning the death of a child fulfilled socio-cultural and religious roles; religious rituals offer hope to address sexual bereavement, and religion was not a foolproof solution to sexual bereavement. The article recommends that the Department of Health deploys and stations registered counselors, social workers, and psychologists in the communities to advocate for and assist communities undergoing trauma and bereavement and to ensure that these bereavement psychological services are within reach of the communities. The article is essential to widen the horizon of literature to future researchers in the domain of sexual bereavement.